Quorum Sensing Plays a Complex Role in Regulating the Enzyme Hydrolysis Activity of Microbes Associated with Sinking Particles in the Ocean - Krupke, Andreas; Hmelo, Laura R.; Ossolinski, Justin E.; Mincer, Tracy J.; Van Mooy, Benjamin A. S. (Frontiers in Marine Science, 2016)
The concentration of atmospheric carbon dioxide is directly linked to the sinking of photosynthetically derived particulate organic carbon (POC) from surface waters to deep waters. This process, known as the marine biological carbon pump, removes carbon from exchange with the atmosphere, thus regulating global climate. Recent evidence suggests that microbial chemical communication systems (e.g. quorum sensing) amongst heterotrophic bacteria associated with sinking POC, significantly influences their hydrolytic enzyme activity and, as such, may affect the efficiency of the biological carbon pump. Here, we present data showing that a class of quorum sensing molecules, acylated homeserine lactones (AHLs) substantially impact hydrolytic phosphatase, aminopeptidase, and lipase activity in samples of sinking particles collected from the Atlantic and Pacific Ocean. Incubations of sinking particles amended with exogenous AHLs showed both stimulated and inhibited rates of activity after 24 hours of incubation, suggesting a critical link between bacterial AHL signaling mechanisms and the rate of POC degradation. Further experiments reveal that hydrolytic pathways could be affected within a few hours of amendment with AHLs, suggesting that microbial communities are able to dynamically modify their metabolic pathways in response to perceived quorum sensing. Finally, the concentration of the AHL amendment also affected hydrolytic activity. Our results indicated that quorum sensing has the potential to influence hydrolytic activity in a range of oceanic environments, but response also vary significantly as a function of the type of AHL, their concentration, and response time. AHL-based quorum sensing may be thought of as a global language among marine bacteria, but it is highly complex.